SCIENCES PRACTICUM IN THE COVID-19 PANDEMIC ERA BY USING A VIDEO TRACKER - Dyah Permata Sari; Wahono Widodo; Madlazim Madlazim (Jurnal Inovasi Pendidikan dan Sains)
The covid-19 pandemic prevention policy has the impact of reducing practicum programs that should be trained for students. In this paper, we show how a video tracker has been effective in achieving straight motion practicum and determining the moon gravity by using e-learning, group discussion, free fall motion video analysis on the moon's gravity acceleration. After the application of the video tracker, the results of quantitative and qualitative data analysis showed that the 2018 class students from physics science education of the State University of Surabaya had significant experiences and commented positively on their experiences. Students show that they are satisfied with the practicum environment by using a video tracker, and the application of a video tracker to determine the moon's gravitational acceleration to improve their skill proficiency in conducting an experiment. The straight motion practicum and the determination of the moon's gravity acceleration by using the video tracker tool described in this paper can be used as a reference to ensure the quality of the online science practicum program during the Covid-19 pandemic. The investigation results show that a video tracker-based practicum environment can train science laboratory skills in the form of predicting, observing, explaining, and analysing video data on scientific phenomena.